On nuclear deterrence the correspondence of Sir Michael Quinlan - Quinlan, Michael (Adelphi (Series) (International Institute for Strategic Studies), 2011)
This timely book, published in the lead up to the 2012-14 decision on Trident renewal, makes available for the first time the late Sir Michael Quinlan's private correspondence on nuclear deterrence. It shows why Sir Michael, as Policy Director and then Permanent Secretary at the Ministry of Defence during the last years of the Cold War, became known as the 'high priest of deterrence': his unparalleled grasp of nuclear strategy, contribution to nuclear doctrine in the UK and NATO, and deep and genuine concern with defence ethics earned him respect and admiration around the world. Even those who challenged him on fundamental questions of strategy and morality (and many of his correspondents fell into this category, as this volume will reveal) recognised his sincere devotion to his cause: the creation of a stable system of east-west nuclear deterrence for the prevention of major war. Before he died in 2009, Sir Michael made it known that he wished for his private correspondence to be published. This book helps fulfil that wish. It presents a selection of the most compelling letters among the many thousands in the Quinlan files. It is intended as a memorial to a brilliant man, an important historical record of British nuclear thinking during the cold war, and a contribution to contemporary debates over the future of nuclear deterrence.